Affective politics in gendered organizations: Affirmative notes on becoming-woman. (January 2017) - Pullen, Alison; Rhodes, Carl; Thanem, Torkild
Current approaches to the study of affective relations are over-determined in a way that ignores their radicality, yet abstracted to such an extent that the corporeality and differentially lived experience of power and resistance is neglected. To radicalize the potential of everyday affects, this article calls for an intensification of corporeality in affect research. We do this by exploring the affective trajectory of 'becoming-woman' introduced by Deleuze and Guattari. Becoming-woman is a process of gendered deterritorialization and a specific variation on becoming-minoritarian. Rather than a reference to empirical women, becoming-woman is a necessary force of critique against the phallogocentric powers that shape and constrain working lives in gendered organizations. While extant research on gendered organizations tends to focus on the overwhelming power of oppressive gender structures, engaging with becoming-woman releases affective flows and possibilities that contest and transgress the increasingly subtle and confusing ways in which gendered organization affects people at work. Through becoming-woman, an affective and affirmative politics capable of resisting the effects of gendered organization becomes possible. This serves to further challenge gendered oppression in organizations and to affirm a life beyond the harsh limits that gender can impose.